Automation of Flexible Migration Workflows - Dirk von Suchodoletz; Klaus Rechert; Randolph Welte; Maurice van den Dobbelsteen; Bill Roberts; Jeffrey van der Hoeven; Jasper Schroder (International Journal of Digital Curation, 2011)
Many digital preservation scenarios are based on the migration strategy, which itself is heavily tool-dependent. For popular, well-defined and often open file formats – e.g., digital images, such as PNG, GIF, JPEG – a wide range of tools exist. Migration workflows become more difficult with proprietary formats, as used by the several text processing applications becoming available in the last two decades. If a certain file format can not be rendered with actual software, emulation of the original environment remains a valid option. For instance, with the original Lotus AmiPro or Word Perfect, it is not a problem to save an object of this type in ASCII text or Rich Text Format. In specific environments, it is even possible to send the file to a virtual printer, thereby producing a PDF as a migration output. Such manual migration tasks typically involve human interaction, which may be feasible for a small number of objects, but not for larger batches of files.